Psychological training in sports - Ramesberger, Reinhold (Quality in Sport, 2022)
The primary task of a coach in competitive sports is the support and guidance of athletes in their development to achieve the individual top level of performance. Therefore, coaches should acquire a working knowledge of all areas affiliated with performance enhancement. Psychological training is one pillar a today´s coach should be familiar with. This article illustrates some components with psychological background knowledge for consideration when applying psychological training. It is imperative for coaches to gain a familiarity with this often neglected facet of training in order to provide support and guidance for athletes on their way to achieve peak performance in competitions along their sports career. With this article science meets real life experience and thus it enhances the body of knowledge for coaches for new thoughts to train elite athletes.